Comparative Study of Phonological Shifts in Pakistani English (PAKE) and Standard British English (SBE): https://doi.org/10.5281/zenodo.16896773 - Ms. Kiran Hussain; Ms. Iqra Azam; Yasir Iqbal; Muhammad Jawad; Arshia Ahmad (Journal of Religion and Society, 2025)
This research investigates the phonological distinctions between Pakistani English (PakE) and Standard British English (SBE), emphasizing the segmental and suprasegmental characteristics that define the phonological aspects of Pakistani English. Utilizing phonetic analysis, sociolinguistic evidence, and established theoretical frameworks, this report examines the impact of regional languages, second language learning processes, and sociocultural influences on the phonological structure of Pakistani English. The study employs a comparative descriptive methodology, integrating both qualitative and quantitative data sourced from literature, surveys, and speech samples. The findings indicate persistent phonological variation in Pakistani English concerning vowels, consonants, stress patterns, and intonation, many of which exhibit foundational interference from Urdu and other indigenous languages. These modifications not only distinguish Pakistani English as a unique linguistic variety but also underscore the evolving nature of English within a postcolonial framework. The results carry significant implications for pedagogy, language theory, and the concept of global Englishes, reinforcing the perspective that Pakistani English is a valid and developing variant of English that merits acknowledgment as a separate academic entity. Keywords: L2 English, Phonological Shifts, Sociolinguistics, Pakistani English, Standard British English, ESL phonology